The crossdresser phenomenon: Between transgender and hobbies (study of crossdresser phenomenon on social media platforms) - Lalu Pradipta Jaya Bahari; Joseph Lere Omiwole (An-Nisa’ Journal of Gender Studies, 2024)
The rise of social media has produced increasingly complex forms of gender identity expression, sparking debates over the boundaries between self-expression, hobby, and gender identity formation in contemporary society. This study aims to analyze the meaning of crossdressing as both a hobby and an exploration of gender identity, as well as the adaptation strategies of the Indonesian crossdresser community in maintaining their boundaries of identity, morality, and social existence in a private manner. This study employed a descriptive qualitative method with Facebook content analysis, triangulation techniques (observation, documentation, and unstructured interviews), data reduction, and interpretation grounded in Judith Butler's queer theory. This study finds that: (1) crossdressing in the Indonesian community carries dual meanings from a simple hobby and self-expression to an early exploration of gender identity potentially leading to permanent transition; (2) the Indonesian crossdresser community firmly separates itself from LGBTQ+ issues, bans pornography, condemns the Crosshijaber incident, and engages in discreet, respectful 'outing' activities. This study concludes that the Indonesian crossdresser community exists within a structural contradiction: the dual meaning of crossdressing (as a hobby versus a pathway to gender transition) and the rejection of LGBTQ+ identity function as adaptation strategies. Nevertheless, public stigma continues to equate crossdressers with LGBT communities. This study extends Social Identity Theory, critiques Western queer assumptions, offers guidance for polite 'outing', and recommends policies distinguishing crossdressing from transgender to reduce stigma.